A fuzzy set approach on students’ answer scripts evaluation / Badrul Hisham Abdullah, Daud Mohamad and Nor Hashimah Sulaiman - Abdullah, Badrul Hisham; Mohamad, Daud; Sulaiman, Nor Hashimah (2004)
In 1965, Zadeh [6] proposed the theory of fuzzy sets. A fuzzy sets approach has been developed to solve problems in which descriptions of activities and observations are imprecise, vague and uncertain. In mathematics, fuzzy sets have triggered new research topics in connection with categorical theory, topology, algebra, analysis, integrals and evaluation. In this paper, the researchers use fuzzy sets approach to evaluate students’ answer scripts in mathematics course. Based on the work of Biswas (1985) [2], Chen & Lee (1999) [3] presented a new method of students’ evaluation compared to the traditional marking method. The researchers will try to improvise some cf the drawbacks found in Chen & Lee’s research and propose some other alternatives in evaluating students’ answer scripts. Chen & Lee utilized a fixed value for each satisfaction levels, not using fuzzy numbers and gave fuzzy marks merely based on the instructor’s opinion. In this paper, the researchers use normalized values to represent some of extreme cases of satisfaction levels and utilize fuzzy numbers to generate more consistent fuzzy marks. After the instructors mark the scripts by using the traditional method, the satisfaction levels of each question will be identified by using fuzzy numbers. Then, the degree of satisfactions of each question will be calculated. The fuzzy marks will be generated to produce the total score. Finally, the fuzzy grade will be obtained. The result that based on the fuzzy sets approach could provide more and better information which portrays the student performance of each question.